Implementasi Pembelajaran Akidah Akhlak Terhadap Pembentukan Karakter Siswa di MTs Negeri Semanu Gunungkidul - Dewi Prasari Suryawati (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2016)
This study was to describe the implementation of moral theology lesson on the formation of character. This study aims to reveal the problems of implementing learning moral theology to the character formation of students facing the teacher, as well as descriptions of the description of the planning, implementation and evaluation of the problems faced by teachers of moral theology. Collecting data using observation technique, interview, and documentation. Processing data using qualitative techniques. This technique is used unyuk dariobservasi process data, interviews and documentation. The results showed that 1) the implementation of character education on planning subjects still characterize moral theology lesson planning and lesson planning has yet to show character. 2) Implementation of the implementation is still conventional. Character education learning in every learning still appoint the same pattern between the first and subsequent learning even planting code execution just is not relevant to the material that is taught by a teacher of the moral theology. Implementation of character education at the stage of the evaluation has been done, however, only use one technique that observation.